How Bullying Can Happen ? Systematic Literature Review of Bullying at the Elementary School Level - Zuhri Ruslan; Kiki Rezkiani (CV. Pusdikra Mitra Jaya, 2023)
Many child abuse cases have gotten attention lately because of the high frequency of occurrence and severity of the cases. This study aims to investigate incidents before and when the bullying happened, the role of schools and parents in bullying, and how to stop bullying. The research method employed was a systematic literature review. The research revealed that bullying happens when there is a lack of teacher supervision and the victim has often been bullied. The bully is often bigger, older, in numbers, and attacks suddenly. The role of parents is to behave after receiving reports of bullying from children. In order to prevent bullying from happening, a program against bullying (anti-bullying) needs to be introduced in schools. The program should target all layers, namely, the students, teachers, staff in the school environment, and parents. The more anti-bullying programs are launched, the more effective they will be in preventing the recurrence of bullying cases.